Epstein-Barr Virus and the Human Leukocyte Antigen Complex - Li, Qingxue (Curr Clin Microbiol Rep, 2019)
PURPOSE: While most adults are infected Epstein-Barr virus (EBV), 3-5% remain uninfected. The human leukocyte antigen (HLA) complex, which controls many pathogens, may influence infection and disease associated with EBV. RECENT FINDINGS: Numerous EBV proteins and miRNAs down-regulate HLA class I and II expression on the cell surface. HLA class II functions as a receptor for EBV entry into B cells. Specific HLA class II alleles correlate with the susceptibility of B cells to EBV infection in vitro and with EBV seropositivity or seronegativity of humans. HLA class I polymorphisms correlate with development and severity of EBV infectious mononucleosis and with the risk of several virus-associated malignancies including nasopharyngeal carcinoma, Hodgkin lymphoma, and post-transplant lymphoproliferative disease. SIGNIFICANCE: These findings indicate that while EBV has evolved to use MHC class II as a receptor for virus entry, polymorphisms in MHC class II and class I influence virus infection and disease.